Unraveling Plant Natural Chemical Diversity for Drug Discovery Purposes - Lautié, Emmanuelle; Russo, Olivier; Ducrot, Pierre; Boutin, Jean A. (Frontiers in Pharmacology, 2020)
The screening and testing of extracts against a variety of pharmacological targets in order to attempt benefiting from the immense natural chemical diversity is a concern in many laboratories worldwide. And several successes have been recorded in finding new actives in natural products, some of which becoming new drugs or new sources of inspiration for drugs. But in view of the vast amount of research on the subject, it is nevertheless surprising that not more drug candidates were found. In our view, it is thus fundamental to reflect upon the approaches of such drug discovery programs and the technical processes that are used, along with their inherent difficulties and biases. Based on an extensive survey of recent publications, we discuss the origin and the variety of natural chemical diversity as well as the strategies having the potential to embrace this diversity. It seemed to us that some of the difficulties of the area could be related with the technical approaches that are used, so the present review begins with synthesizing some of the more used discovery strategies, exemplifying some key points, in order to address some of their limitations. Thereby, it appears that one of the challenges of natural products-based drug discovery programs should be an easier access to renewable sources of plant-derived products. Maximizing the use of the data together with the exploration of chemical diversity while working on reasonable supply of natural product-based entities could be a way to answer this challenge. We thus suggested alternative ways to access and explore part of this chemical diversity with in vitro cultures. We also reinforced how important it was organizing and making available this worldwide knowledge in an “inventory” of natural products and their sources. And finally, we focused on strategies based on synthetic biology and syntheses that allow to reach industrial scale supply. Approaches based on the opportunities lying in untapped natural plant chemical diversity are also considered.